ТАЪЛИМНИ АХБОРОТЛАШТИРИШ ШАРОИТИДА РАҲБАР КАДРЛАР БОШҚАРУВ КОМПЕТЕНЛИГИНИ РИВОЖЛАНТИРИШНИНГ НАЗАРИЙ-МЕТОДИК АСОСЛАРИ - Отамуродов, Ғ.Р.; Эргашев, Ё.С. (SCIENCE and SOCIETY, 2020)
The article gives guidance on the use of information technologies in assurance of education quality in higher education and improvement of its efficiency, functional simulation of the integration system between higher education institutions, the formation and development of managerial competencies of the personnel, and organization of the system work in the conditions of educational Informatization.
Keywords: information; technology; leader; competency; integration